Pengembangan Modul Berbasis Warisan Budaya Tak Benda Batik Subtema Peristiwa Mengisi Kemerdekaan - Uliatul Murtasidah; Priyono Tri Febrianto (Jurnal Pengembangan dan Evaluasi Pendidikan, 2024)
The purpose of this study was to determine the validity, effectiveness, and practicality of the module based on intangible cultural heritage, batik, sub-theme of events filling independence for class V SDN Tagungguh 3, Tanjungbumi, Bangkalan. This study uses the Research and Development (R&D) method using the 4D development model (Define, design, development, disseminate). Limited trial activities used as many as 8 students as subjects, while implementation trials used as many as 29 students as subjects. Module validity was reviewed based on the results of expert validation, where there were 4 validators in this study, namely teaching material design experts, learning design experts, materials experts, and language experts. The validity of this module obtains a value of 90% with a very valid category. The effectiveness of the module is reviewed from the evaluation of student learning and is declared complete classically with a score of 89.65%, thus the module is declared valid. While the practicality of the module is seen from the student response questionnaire and the implementation of learning. The student response questionnaire obtained a score of 97.5% in the very good category, and learning implementation obtained a score of 96% in the implemented category, thus the module was declared practical.